A new treehopper genus and species from Puerto Rico (Hemiptera: Membracidae: Stegaspidinae) with notes on other Caribbean Membracidae - Dietrich, Christopher H. (Zootaxa, 2017)
Borinctolania sakakibarai, n. gen. and n. sp. from Puerto Rico is described, illustrated, and placed in the subfamily Stegaspidinae. The new genus is morphologically similar to the previously described endemic Caribbean genera Antillotolania Ramos, Deiroderes Ramos and Togotolania Cryan & Deitz, all of which remain unplaced to tribe. A key to the Caribbean treehopper genera that lack a posterior pronotal process and a species checklist for this group are provided, and relationships of the new genus to other membracids are discussed.